Relationship between Knowledge, Attitude and Family Support with Exclusive Breastfeeding - Meike Julesa Angreni; Rizki Amalia Rizki; Andini Zuitasari; Ahmad Arif (Universitas Islam Jember, 2022)
Exclusive breastfeeding is an important factor in infants, especially early breastfeeding (colostrum) because it's rich in antibodies which have an effect on reducing the risk of death. Government efforts to support an increase in exclusive breastfeeding have issued agreements or various recognition both globally and nationally aimed at protecting, and supporting breastfeeding. This is in accordance with the Sustainable Development Goals (SDGs) of the three second targets, namely 2030, ending preventable infant and under-five mortality. This study aims to determine the relationship between knowledge, attitudes and family support simultaneously with exclusive breastfeeding at Sungai Menang Health Center, Ogan Komering Ilir Regency in 2021. An analytical survey research with cross sectional. The population in this study were mothers who had babies aged 7-12 months totaling 389 respondents and the sample size was determined by the slovin formula. Obtained a sample of 79 respondents, the sample was taken by purposive sampling technique. Data analysis used chi square statistical test with research results p value value (0.05). The results of this study were from 33 respondents who had good knowledge of exclusive breastfeeding as many as 22 respondents (66.7%) with p value = 0.003, 31 respondents who got a positive attitude with exclusive breastfeeding as many as 19 respondents (61.3%) p value = 0.04, meanwhile, 26 respondents who received family support by exclusive breastfeeding were 19 respondents (73.1%) p value = 0.001. Midwives are expected to increase counseling and socialize the exclusive breastfeeding program to the community.